(untitled) (Aporte Santiaguino, 2020)
Based on analytical study (in order to establish cause-effect relationship of seismic events) I propose the Seismic Energy Theory, according to which a seismic event result of the disturbance of the accumulated external energy (solar energy -photons) through the transit of internal energy, whose sudden movement -due to the fact that the electrons repel each other- generates seismic waves with attenuating and vibratory characteristics, through which there is energy transport in the form of vibration without that matter is displaced and is perceived as seismic movements; for such eects, the internal energy has a constant path in the form of seismic circuits, in which the climate and soil have a determining role.